Characterization of the endogenous promoters in Yarrowia lipolytica for the biomanufacturing applications. (January 2023) - Wang, Chang; Lin, Mingxin; Yang, Zhiliang; Lu, Xueyao; Liu, Yinfang; Lu, Huizhi; Zhu, Jiang; Sun, Xiaoman; Gu, Yang
Abstract: Yarrowia lipolytica, an oleaginous yeast with the GRAS status, has been developed as a platform for the chemical production. Promoter engineering is an important approach to regulating gene expression at the transcriptional level, which is of great significance in constructing microbial cell factories. Although some work on promoter study has been carried out in Y. lipolytica, obtained achievements still need further replenishment and development, compared explicitly with Saccharomyces cerevisiae, Bacillus subtilis, and other microorganisms. For this, we screened 81 endogenous promoters in Y. lipolytica, mainly involved in carbon metabolism and nitrogen metabolism. As a result, we obtained 15 strong promoters, 41 medium strength promoters, and 25 weak promoters, with the strength spanning from 0.06 % to 1.60-fold of PTEF promoter. Moreover, as a proof-of-concept, the identified promoter library was applied for expressing UDP-glycosyltransferase to produce salidroside, resulting in a production of 95.64 mg/l in shake flask, which is 3.92-times that of the parental strain. In general, our study provides a unique and available endogenous promoter library for Y. lipolytica . Graphical Abstract: ga1 Highlights: Obtaining a promoter library with the strength spanning from 0.06 % to 160 % of PTEF . Characterizing 15 strong promoters, 41 medium promoters, and 25 weak promoters. The strongest promoter is PMnDH2 ( YALI0D18964g ), 1.60-fold of the strength of PTEF . The weakest promoter is PPHO89 ( YALI0E23859g ), 0.06 % of the strength of PTEF .